Breakeven Analysis Under Absorption Costing. - Solomons, David (The Accounting Review, 1968)
The simplistic assumptions underlying the classical breakeven chart have long been recognized as unsatisfactory. Many of those who have felt this dissatisfaction have been content to apologize for the shortcomings of breakeven analysis. Failure to grasp the implications of the direct cost philosophy for breakeven analysis leads to misunderstandings. For instance, it is commonly said that the classical breakeven chart assumes an identity of sales and production quantities. In fact, no such assumption is necessary, for under direct costing, all fixed costs are to be covered out of current revenue; no fixed costs are inventoriable. Although, under direct costing, changes in inventory during a period do not affect the breakeven point, it does turn out that, under absorption costing, a firm can break even while achieving an identity of production and sales only at the traditional breakeven sales level. The analysis above is quite symmetrical as between increases and decreases in inventory so long as there is no change in cost conditions from period to period.